Beneficial effects of Stevioside on AGEs, blood glucose, lipid profile and renal status in streptozotocin-induced diabetic rats - Aswar, Urmila; Gogawale, Vinayak; Miniyar, Pankaj; Patil, Yugendra (Journal of Applied Biomedicine, 2019)
The advanced glycated end products (AGEs) are formed in the diabetic patients; it is a major cause of macrovascular and microvascular complications in diabetes. Clinically there is no treatment available for the AGEs. Stveoside (Stv), a sweetener has potent anti-diabetic and anti-oxidant activity. Hence, we investigated its use in prevention of AGEs formation using in vitro and in vivo models. Diabetes was induced by streptozotocin (STZ). These rats were kept without treatment till blood HbA1c was markedly increased. They were then divided into 5 groups and treated orally with vehicle or Metformin (MET) or Stv respectively for 28 days. Every 7th day, animals were tested for body weight and blood glucose (BG). On the last day of treatment, all the groups were evaluated for physiological and biochemical parameters, histopathology and AGEs; N-carboxymethyl-lysine (CML) estimation. Stv showed inhibition of AGEs in in vitro as well as in in vivo respectively. Positive effects were seen on the BG, lipid profile and urine parameters as well it showed reduced formation of CML. It also showed antihyperglycaemic, antihyperlipedemic and nephroprotective activities. The present study provides scientific rationale for the use of Stv as a sweetener with additional benefits in diabetes.
Keywords: AGEs; Diabetes; Diabetes complications; N-carboxymethyl-lysine; Stevioside; Streptozotocin

Characterisation of hyper tolerant Bacillus firmus L-148 for arsenic oxidation - Bagade, Aditi; Nandre, Vinod; Paul, Dhiraj; Patil, Yugendra; Sharma, Nisha; Giri, Ashok; Kodam, Kisan (Environmental Pollution, 2020)
Groundwater arsenic pollution causes millions of deaths worldwide. Long term natural and anthropogenic activities have increased arsenic levels in groundwater causing higher threats of arsenic exposure. Arsenic hyper-tolerant Firmicute Bacillus firmus L-148 was isolated from arsenic limiting Lonar lake soil, which tolerated more than 3 M arsenic and could oxidize 75 mM arsenite [As(III)] in 14 days. It oxidized As(III) in presence of heavy metals and had unusual pH optima at 9.2. B. firmus L-148 was studied at the biochemical, protein, genomic and transcript level for understanding its arsenic oxidizing machinery. The proteomic and transcript analysis exhibited the presence of ars and aio operon and supported the inducible nature of ars operon. Robust, hyper-tolerant, fast As(III) oxidizing, least nutrient requiring and multi-metal resistance qualities of the strain were used in microcosm studies for bioremediation. Artificial groundwater mimicking microcosm with 75 mM As(III) was developed. Modulation of carbon source, iron and multi metals affected growth and As(III) oxidation rate. The As(III) oxidation was recorded to be 77% in 15 days in presence of sodium acetate and Fe ions. This microcosm study can be explored for bioremediation of arsenic contaminated water and followed by precipitation using other methods. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Arsenic hyper-tolerance; Lonar lake; Microcosm studies; Multi-metal resistance; Next generation sequencing